Gotham City sirens songs of the sirens - Dini, Paul.; Bedard, Tony.; March, Guillem 1979-. (New York DC Comics, 2010)
Catwoman, Poison Ivy, and Harley Quinn are tired of playing by other people's rules. As their alliance with the Riddler continues, they will do anything to find out which villain is targeting them for death.
Originally published in single magazine form in Catwomen #83 and Gotham City sirens #8-13.
Keywords: Graphic novels; Superhero comic books, strips, etc